Evaluation of Serum Catalase Activity and Malondialdehyde Level as Stress Oxidative Biomarkers among Iranian Welders - Sattarahmady, Naghmeh; Heli, Hossein; Mehdizadeh, Ali Reza; Yarmohammadi, Hossein; Mortazavi, Seyed Mohammad Javad (Galen Medical Journal, 2015)
Background: Oxidant/antioxidant imbalance results in oxidative stress which plays a major Â role in many diseases. Inhalation of metal-enriched fumes and exposure to electromagnetic Â fields of welding device could induce oxidative stress in welders. Therefore, it is necessary to determine the level of oxidative stress among welders. Our study is aimed at estimating serum catalase and Malondialdehyde (MDA) levels in Iranian welders. Materials and Methods: Serum catalase activity and MDA levels were measured in 30 Iranian welders and 30 healthy non-welder subjects via catalase and MDA kit (Abcam). Results: The catalase activity (mU/L) and MDA levels (nmol/mL) were found to be 7.19Â±2.30 and 0.97Â±0.55, respectively in welder subjects, 10.73Â±1.08, and 0.58Â±0.38 in the control subjects. Catalase activity among welders was significantly lower than the control subjects (P<0.0001). In addition, plasma MDA level was significantly higher in welders, compared to the control subjects (P=0.0028). There was no significant difference between welder subgroups when the catalase activity and plasma MDA levels were compared. Conclusion: This study indicates that oxidant/antioxidant balances alter in Iranian welders. In other words, these results imply that the threshold limit of the resistance of the welder body against oxidative stress and damage has decreased. [GMJ. 2015;4(3):62-66]